The relationship between economic growth, foreign direct investment, trade openness, and unemployment in South Asia - Anh Tru Nguyen (Asian Academy of Management Journal, 2022)
The aim of this article is to investigate the relationship between gross domestic product (GDP) growth rate, inflow foreign direct investment (FDI), trade openness, and unemployment in five South Asian countries between 1998 and 2017 using a vector autoregressive model. It has been empirically found that GDP growth rate and unemployment have positive relationships with FDI. Results demonstrated that there is a directional relationship running from FDI to GDP growth rate and from FDI to unemployment. The study shows that there is a long-run relationship between GDP growth rate, FDI, trade openness’s and unemployment in the region. Macro policies are recommended to accelerate economic growth, FDI, and reduce unemployment rate in South Asia.